Effect of the drop out fuse connection scheme on the overvoltage and the surge arrester in a distribution system - Chaiyaporn Lothongkam; Theerasak Patcharoen; Suntiti Yoomak (My University, 2023)
Overvoltage is a critical problem of Thailand' distribution system. The electrical protection device in the distribution system needs to be able to support this level of overvoltage. In the distribution system connecting the Chachoengsao2 substation and the Bang Khla substation, the overvoltage from a ferro resonance phenomenon affects the surge arrester directly. This research studies the effect of the drop-out fuse connection scheme on the voltage and surge arrester using the RMS/EMT Simulation mode in the DIgSILENT program. Normally, the surge arrester withstands a voltage of 1.9 p.u. of the phase voltage. If the overvoltage in the distribution system is higher than the voltage that the surge arrester can withstand, the surge arrester can be damaged. Therefore, it is necessary to study and analyze the drop out fuse insertion pattern that affects the overvoltage in the distribution system to understand the causes of overvoltage problems and their effects on each type of electrical protective equipment.
Keywords: Overvoltage; Surge arrester; Fuse (electrical); Voltage drop; Lightning and Electromagnetic Phenomena